Malaysia Good Design Award for Product Floating Crab Farming - Saiful Bahari, Hj Mohd Yusoff; Ibrahim, Zalina (Majlis Rekabentuk Malaysia, Kementerian Perdagangan Antarabangsa dan Industri, 2020)
The first award ever granted to university in Malaysia, and UNIMAS has been chosen for its product innovation design, the Floating Crab Farming product. This is a prestige award that recognizes the uniqueness and practicality of design in a product innovation.